2019 IEEE Intelligent Transportation Systems Conference (ITSC) 2019
DOI: 10.1109/itsc.2019.8917061
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Convolutional Neural Networks for Railway Catenary Support Components Monitoring

Abstract: The development of algorithms for detecting failures in railway catenary support components has, among others, one major challenge: data about healthy components are much more abundant than data about defective components. In this paper, virtual reality technology is employed to control the learning environment of convolutional neural networks (CNNs) for the automatic multicamera-based monitoring of catenary support components. First, 3D image data based on drawings and real-life video images are developed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The monitoring is achieved using high-definition cameras installed on dedicated inspection vehicles, with image capturing primarily taking place at night to avoid the interference of complex daytime backgrounds. It is worth noting that, while early papers focused on the feasibility of using deep learning-based computer vision to monitor catenary supportive components [20,21], recent works, especially in 2022, have focused more on improving the precision and performance of these approaches for specific components. For example, papers [8,39] have adopted advanced methods to improve the accuracy of insulator defect detection.…”
Section: Monitoring Targetsmentioning
confidence: 99%
“…The monitoring is achieved using high-definition cameras installed on dedicated inspection vehicles, with image capturing primarily taking place at night to avoid the interference of complex daytime backgrounds. It is worth noting that, while early papers focused on the feasibility of using deep learning-based computer vision to monitor catenary supportive components [20,21], recent works, especially in 2022, have focused more on improving the precision and performance of these approaches for specific components. For example, papers [8,39] have adopted advanced methods to improve the accuracy of insulator defect detection.…”
Section: Monitoring Targetsmentioning
confidence: 99%
“…Tables 3 and 4, whose structure and aim are described in Section III-E, summarise the papers we found within this Railway Area. Catenary Support Device [95], [96], [97] [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110] [111], [112], [113], [114], [115], [116] Pantograph & Arcs [117], [118] [101], [119], [120], [121] [122], [123], [124] Catenary Wires [125], [126], [127], [128], [109] [129]…”
Section: Pantograph and Catenarymentioning
confidence: 99%
“…These data sources make it possible to increase the level of details about the condition of the railway infrastructure obtained during inspection programs. The literature so far of 3-D point cloud data for railway applications is somewhat limited [15]- [18]. Han et al [19] used 3-D point cloud data to detect the SPCCDs, as shown in Fig.…”
Section: (B)mentioning
confidence: 99%